The Approach in Evaluating Students' Alternative Assessment for Interdisciplinary Courses - Farah, Zaini; Adibah, Yusuf; Siti Khatijah, Zamhari (2020)
Interdisciplinary integration is where the curriculum is organized through common learning’s cross disciplines. They chunk together the common learning’s embedded in the disciplines to emphasize interdisciplinary skills and concepts. An interdisciplinary approach is the developed approaches that are now commonly used in a wide spectrum of disciplines. It involves the combining of two or more academic disciplines into one activity, also draws knowledge from several other fields. This approach was applied for Social Sciences students who enrol in development planning and management program in UNIMAS. Three courses were combined which are Social and Environmental Impact Assessment, Geographical Information System and Sociology Development. There are many ways in assessing interdisciplinary courses and one of them are through fieldwork. Before the execution of fieldwork, there are elements that need to be considered in choosing the site and assessment. The elements must fit the purpose of these three courses. It involves the combining of two or more academic disciplines into one activity, also draws knowledge from several other fields. This article discusses the elements and the feasible approach in evaluating the alternative assessment for interdisciplinary courses.